Implementasi Model Pembelajaran mendalam untuk Mengingkatkan Kemampuan Interpretasi dan Memahami Isi Teks pada Kelas 5B SDN 2 Cimerang: Implementasi Model Pembelajaran mendalam untuk Mengingkatkan Kemampuan Interpretasi dan Memahami Isi Teks pada Kelas 5B SDN 2 Cimerang - Alifah, Nadiatul; Kohar Pradesa (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This study aims to determine the improvement of the ability to interpret and understand the contents of elementary school students' texts with the Deep Learning Model. The Deep Learning Model includes meaningful, mindful, and Joyful in the context of Education. The subjects assessed were grade 5B students at SDN 2 Cimerang. The methods used were interviews, observations, documentation and literature studies. The deep learning approach emphasizes critical learning, linking new information to existing knowledge, and its application in real contexts. The implementation of deep learning at the elementary and secondary levels ultimately has a positive impact on student learning outcomes. The results of the Deep Learning Model are expected to be used as an effort to improve the ability to interpret and understand the contents of elementary school students' readings.